2012
DOI: 10.1024/0301-1526/a000223
|View full text |Cite
|
Sign up to set email alerts
|

Achenbach’s syndrome revisited

Abstract: We stress the need for greater awareness among clinicians of the harmlessness of the condition in order to avoid misdiagnoses and dispensable diagnostic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Another explanation of the reduced blood flow might be compression by the hematoma [4]. In contrast to these dynamic causes of hypoperfusion, hypoplasia of the ulnar artery on the same hand side has also been described [10]. In our patient also lower arm arteries were rather small, and blood flow was reduced even outside of an attack.…”
Section: Case Reportmentioning
confidence: 52%
See 3 more Smart Citations
“…Another explanation of the reduced blood flow might be compression by the hematoma [4]. In contrast to these dynamic causes of hypoperfusion, hypoplasia of the ulnar artery on the same hand side has also been described [10]. In our patient also lower arm arteries were rather small, and blood flow was reduced even outside of an attack.…”
Section: Case Reportmentioning
confidence: 52%
“…Achenbach's syndrome occurs more frequently in women than in men [5,9,10]. Affected patients are younger than those who suffer from peripheral vascular disease, but the onset might be later than that of Raynaud's syndrome [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Singer [19] favoured the hypothesis of a vasomotor disorder, and the association of PFH with Raynaud phenomenon was recently brought into focus by Thies et al [21] who found three patients with Raynaud in a series of eight women with PFH. This is consistent with the epidemiological associations we found, both with Raynaud phenomenon and with a history of chilblains.…”
Section: Discussionmentioning
confidence: 99%